On the issue of analysis of legal documents on information security of automated systems of internal affairs bodies of the Russian Federation to assess the level of their security - E. A. Rogozin; I. G. Drovnikova; A. O. Yefimov; V. R. Romanova (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective.  When solving a scientific problem related to assessing the security of automated systems of internal affairs bodies, in particular, when developing a methodology for quantifying protected automated systems of internal affairs bodies, the first stage of the solution is the analysis of international, Russian, as well as departmental legal documents on information security ( IS) of automated systems of internal affairs bodies of the Russian Federation (AS ATS of the Russian Federation), based on the results of the analysis of which it is necessary to develop a methodology for quantifying the level of security of the ATS of the Russian Federation.Method. In the course of the work, an analysis was made of international, Russian, as well as departmental legal documents on information security of the ATS of the Russian Federation.Result. An exhaustive list of literature has been obtained, including international, Russian, as well as departmental legal documents on information security of the RF ATS AS.Conclusion. An analysis of international, Russian, as well as departmental legal documents on information security of the ATS of the Russian Federation showed that the documents on the protection of information of the ATS of the Russian Federation, as well as the methodology for quantifying the level of security of these systems, have been developed insufficiently, in particular, they are absent a system of indicators, as well as mathematical models and algorithms for assessing the level of security of the ATS of the Russian Federation, which requires significant improvement of these documents.